Effect of a multivitamin complex and probiotic blend in drinking water before and after vaccination on performance traits, blood biochemistry and humoral immune response of broilers - Jafarpour, N.; Javandel, F.; Gamboa, S.; Seidavi, A.; Tufarelli, V.; Mazzei, D.; Laudadio, V. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
This study was conducted in order to investigate the effects of a multivitamin complex and probiotic blend in drinking water before and after vaccination on growth performance, carcass traits, blood biochemical parameters and humoral immune response of broiler chickens. A total of 150 one day-old male broiler chicks (Ross 308) were randomly allocated to five treatment groups, with three replicates (10 birds per replicate) in a completely randomized design. Experimental treatments consisted of: 1) a basal diet and drinking water without any additives as control (C); 2) C + drinking water + multivitamin complex from 2 days before vaccination until 3 days after vaccination; 3) C + drinking water + multivitamin complex for 3 days after vaccination; 4) C + drinking water + probiotic blend from 2 days before vaccination until 3 days after vaccination; and 5) C + drinking water + probiotic blend for 3 days after vaccination. In the whole experimental period, feed intake, body and thigh weight and abdominal fat were significantly affected (P<0.05) by dietary treatments. On the contrary, no significant effect was observed on carcass characteristics, feed conversion ratio, blood parameters, antibody production against SRBC and IgG. The titer of IgM was higher in treatment (2) than other treatments at 28 d of age (P<0.05). In conclusion, a multivitamin complex supplied in drinking water for 2 days before vaccination till 3 days after vaccination is enable to improve broiler performance and immunity.